Nitrogen doses in rice grown in a tropical lowland - Lopes, Marilia Barcelos Souza; Oliveira, Taynar Coelho de; Ramos, Danilo Pereira; Tonello, Leila Paula; Alexandrino, Cassia Mara dos Santos; Fidelis, Rodrigo Ribeiro (Comunicata Scientiae, 2015)
The rice plant is characterized by having high nutrient demand, being nitrogen (N) the main limiting factor to its productivity. The objective of this study was to evaluate the response of two rice cultivars according to doses of nitrogen fertilization. The experiment was carried out in an irrigated lowland area with hydromorphic soil (humic gleysol) at the region of Formoso do Araguaia-TO, Brazil. The experiment design consisted of five N doses (30, 60, 90, 120 and 150 kg ha -1) applied as urea, and two rice cultivars (Irga-424 and Irga-423). Each experimental plot consisted of twenty-seven lines with 15 m in length, spaced 0.17 m between rows. The useful plot size was made up of four central lines with two linear meters of length. The evaluated characteristics were plant height, number of panicles per m2 , grain yield in kg ha -1, hundred grain mass in g, nitrogen content in dag kg-1, and total chlorophyll index in CFI. Data were submitted to variance analysis and regression at 5% probability by F test. The maximum yield was obtained at a dose of 96 and 126.38 kg N ha -1 for Irga- 424 and Irga-423, respectively. The highest grain yield was 7800 and 5860 kg ha -1 for Irga-424 and Irga-423, respectively.